Transanal Minimally-Invasive Surgery (TAMIS): Experience with No Closure of the Rectal Defect - Naiderman,Diego (2021)
Abstract Background In transanalminimally-invasive surgery (TAMIS), the closure of the rectal defect is controversial, and endoluminal suture is one of the most challenging aspects. The goal of the present study is to evaluate the short- andmedium-term complications of a consecutive series of patients with extraperitoneal rectal injuries who underwent TAMIS without closure of the rectal defect. Materials and Methods A prospective, longitudinal, descriptive study conducted between August 2013 and July 2019 in which all patients with extraperitoneal rectal lesions, who were operated on using the TAMIS technique, were consecutively included. The lesions were: benign lesions ≥ 3 cm; neuroendocrine tumors ≤ 2 cm; adenocarcinomas in stage T1N0; and adenocarcinomas in stage T2N0, with high surgical risk, or with the patients reluctant to undergo radical surgery, and others with doubts about complete remission after the neoadjuvant therapy. Bleeding, infectious complications, rectal stenosis, perforations, and death were evaluated. Results A total of 35 patients were treated using TAMIS without closure of the defect. The average size of the lesionswas of 3.68±2.1 cm(95% confidence interval [95%CI]: 0.7cmto 9 cm), their average distance from the anal margin was of 5.7±1.48cm, and the average operative time was of 39.2±20.5 minutes, with a minimum postoperative follow-up of 1 year. As for the pathologies, they were: 15 adenomas; 3 carcinoid tumors; and 17 adenocarcinomas. In all cases, the rectal defect was left open. The overall morbidity was of 14.2%. Two patients (grade II in the Clavien-Dindo classification) were readmitted for pain treatment, and three patients (grade III in the Clavien-Dindo classification) were assisted due to postoperative bleeding, one of whom required reoperation. Conclusion The TAMIS technique without closure of the rectal defect yields good results, and present a high feasibility and low complication rate.